PENGARUH KOMPENSASI TERHADAP MOTIVASI KERJA, KEPUASAN KERJA, DAN KINERJA KARYAWAN (Studi pada Karyawan Tetap PT. Otsuka Indonesia di Lawang, Malang) - Muhammad Yusril (Jurnal Ilmiah Mandala Education (JIME), 2017)
The background of this research is the compensation policy of a company's performance helped determine the direction of its employees to support the company's goals. Compensation is one of the important factors to be able to attract potential employees. Work motivation is also another factor that must be considered in addition to compensation for employees of the company to realize the goals of the organization, the following job satisfaction. Those three things are important factors in the company to support employee performance. This study aimed to examine the effect of compensation on work motivation, job satisfaction, and performance of employees on permanent employees of PT. Otsuka Indonesia in Lawang, Malang. Formulated several hypotheses of the study are (1) Is compensation a significant effect on work motivation? (2) Is compensation a significant effect on job satisfaction? (3) Is compensation a significant effect on the performance of the employee? (4) Is the work motivation have a significant effect on job satisfaction? (5) Is a significant effect on employee motivation employee performance ?, (6) Is job satisfaction significantly influence employee performance ?. This research is explanatory research with quantitative approach. The technique of collecting data from questionnaires and interviews. Research methods to process the data using path analysis. Based on the results of the study found a significant effect of compensation on employee motivation PT. Otsuka Indonesia, there is a significant effect of compensation on employee job satisfaction of PT. Otsuka Indonesia, there is a significant influence on the performance of the compensation of employees of PT. Otsuka Indonesia, there is a significant effect of work motivation on employee job satisfaction of PT. Otsuka Indonesia, there is a significant influence on the performance of the work motivation of employees of PT. Otsuka Indonesia, and found no significant effect of job satisfaction on the performance of employees of PT. Otsuka Indonesia. Employees of PT. Otsuka Indonesia are already satisfied with the salary he got in a long time felt it would be a regular thing. So prone to reduced performance, because by working casual or work hard to remain earned his salary by the same amount. Employees of PT. Otsuka Indonesia also feel responsibility for the work carried out so far have not been entirely in accordance with his ability means that the principle of "the right man on the right place" has not been felt by the employees of PT. Otsuka Indonesia. Interesting work and the work has not felt like a hobby for PT. Otsuka Indonesia as yet incompatibility refers to the responsibility of the employee's ability to be felt